Using Cartoon Story Maker 1.1 in Developing Writing English Skills in EYL Classrooms - Jenny Elvinna Manurung (Jurnal Didascein Bahasa, 2015)
ABSTRACT: This paper highlights the integrating technology, cartoon story maker 1.1 in EYL classrooms in developing their writing English skills. It leads students to be creative, to work independently, to express themselves and to feel part of the learning process by actively participating in it. This study used the quasi experimental research. The population of the study is VI grade students of SD Methodist 2 Palembang in the academic year 2014/2015. The purposive sampling is used on this study. In analyzing the data of the students’ achievement, the writer compared the results of the pre-test and post-test of each group to see whether they made progress and to find out the significance of the differences between their pre-test scores and their post-test scores. The result of the independent sample t-test: the value of t-obtained was 11.364. At the significance level 0.05 in two tailed testing with df =38, the critical value of t-table= 1.686. Since the value of t-obtained (11.364) was higher than the critical value of t-table (1.686). It means that there was significant difference in writing transactional and interpersonal conversation achievement between the experimental group and the control group. Key words: cartoon story maker V. 1.1, EYL classrooms.